Multisystem inflammatory syndrome, probably associated with SARS-CoV-2, complicated by thrombus in the right atrium, in a child - O. V. Usachova; O. V. Konakova; Ye. A. Silina; N. V. Vorobiova (Zaporozhye State Medical University, 2022)
Aim. Clinical case report of multisystem inflammatory syndrome, probably associated with COVID-19 and complicated by large thrombus in the right atrium in a child highlights the problems of monitoring, treatment, and the possibility of their solution. Presentation of a clinical case. We demonstrate one of the cases of multisystem inflammatory syndrome (MIS-C), which meets WHO criteria. In a child with a severe course of the disease and symptoms of hyperinflammation, on the 16th day from the onset of the disease, a positive effect was registered on the introduction of human normal immunoglobulin for intravenous administration and glucocorticosteroids. But on the day 27 of the disease, despite administration of anticoagulant therapy, a large blood clot was found in the right atrium cavity. Operation was performed with removal of the thrombus from the right atrium under artificial blood circulation and the child was discharged in satisfactory condition to continue treatment in an outpatient setting on the day 56 of the disease. Conclusions. Timely diagnosis of MIS-C in children with fever, signs of inflammation and organ dysfunction during the pandemic spread of COVID-19 and reasonable administration of intravenous immunoglobulin and steroids may reduce the inflammatory response and improve the prognosis. It is also important to conduct population-based prospective studies to optimize thromboprophylaxis in children with COVID-19 and MIS-C.